Application of the dynamic analysis of the wave field for the purpose of identification tectonic and situation geodinamiche-skoy in the field povkhovsky petroproductive complexes - Y. Yu. Taymeneva; A. V. Lyalin (Вестник Северо-Кавказского федерального университета, 2022)
The article presents a view on investigation of the tectonic-dynamic situation, detecting specific features about the tectonic model from the stance of subvertical destruction zones emergence, which are related to increased oil fraction in the liquid.